Analisis Dampak Abrasi Pantai Terhadap Aktivitas Sosial-Ekonomi Masyarakat di Pantai Ujung Baru Serang, Kabupaten Pinrang - fathul rahman mnur (xxxx-xxxx, 2026)
This study aims to analyze the impact of coastal abrasion on the socio-economic conditions of the community and identify the forms of adaptation undertaken at Ujung Baru Serang Beach, Data Village, Duampanua District, Pinrang Regency. The study employed a qualitative descriptive method, with data collection techniques including interviews, observation, and documentation with affected communities and village officials. The data obtained were analyzed through stages of reduction, presentation, and drawing conclusions to describe the impact of abrasion and community adaptation strategies. The results indicate that coastal abrasion causes damage to fishponds, decreased fishing catches, loss of tourism potential, and increased household economic burdens due to damage to homes and production facilities. Furthermore, abrasion leads to population displacement, reduced interaction between residents, and weakened collective community activities. In response to these conditions, the community has adapted by seeking alternative sources of income, such as trading, starting small businesses, or working odd jobs. Women have turned to selling seafood in traditional markets. This adaptation has helped meet daily needs, but income remains low and unstable, thus leaving the community's socio-economic resilience vulnerable.